PENGEMBANGAN KOGNITIF ANAK USIA DINI MELALUI METODE BERMAIN MEDIA PANSITUNG DI RA KENTENGSARI KABUPATEN MAGELANG - Farida Khusniawati; Asih Puji Hastuti; Sigit Tri Utomo (Institut Islam Nahdlatul Ulama Temanggung, 2021)
Abstract This study aims to 1) develop cognitive aspects through the method of playing pansitung media for children of RA Kentengsari; 2) identify supporting factors and inhibiting factors for the cognitive development of children of RA Kentengsari. The research method uses a descriptive qualitative research approach. The researcher uses three data collection techniques, namely observation, interviews, and documentation, to test the validity of the data by using triangulation of sources. The results of research in early childhood cognitive development through the pansitung media playing method at RA Kentengsari, Windusari District, Magelang Regency can be said to have developed as expected. The findings revealed that: 1. the child could compose number symbols, count with his fingers using the finger method, and write numbers correctly. 2. Factors supporting cognitive development at RA Kentengsari are heredity, environmental factors, formation factors, interest and talent factors, maturity factors, and freedom factors, while the inhibiting factors for cognitive development are due to poor parenting, parents' being authoritarian , physical disability, lack of affection, and uncomfortable environment.